Luther und die Reformation in internationalen Geschichtskulturen Perspektiven für den Geschichtsunterricht - Bernhard, Roland (2017)
What do texbook write to the topic reformation? How do they interprete the legacy of Martin Luther? How do they depict the role of the catholic church? This book proviedes answers to these questions in the ligth of discourses within history education research.